¿Es compatible la durabilidad con la sostenibilidad en la industria de la construcción? - Garcés Terradillos, P.; Zornoza, E.; Baeza Brotons, F.; Galao, O.; Payá, J. (Revista ALCONPAT, 2012)
This paper presents the results obtained in the evaluation of a series of properties related to durability and strength of steel reinforced cement mortars partially substituted with different agricultural and industrial residues presenting pozzolanic activity: sewage sludge ash (SSA), fly ash (FA), spent catalytic cracking catalyst (FCC) and rice husk ash (RHA). These results show that it is possible to achieve a sustainable development in the construction industry. This can be obtained by reducing the clinker content in cement and reusing industrial and agricultural byproducts with an appropriate level of durability of the construction materials fabricated from them. Keywords: durability; sustainability; industrial byproduct; agricultural byproduct.